Analisis Kontrak Kerja Pengadaan Barang Perspektif Standar Islami Rumah Sakit Muhammadiyah-Aisyiyah (Sirsma) : Studi di RSU UMM - Hamdan Hadi Sumadyo; Idaul Hasanah; Djoko Tritjahjana (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The urgency of this research lies in strengthening the management of procurement contracts for goods based on Islamic principles to support the identity of UMM General Hospital as an Islamic hospital. The focus of the study covers the regulation of Islamic principles in SIRSMA, the level of compliance of contractual practices particularly regarding riba and risywah as well as the factors triggering both. The research aims to analyze the compliance of contracts with Sharia principles through a normative legal approach encompassing legislative, conceptual and case study methods, utilizing secondary data from literature reviews. The results indicate that although SIRSMA has established Sharia contracts, they may potentially lead to legal consequences regarding the validity and implementation of the contracts. Therefore, strengthening internal policies and oversight is necessary to avoid practices that contradict Islamic principles.